SEMI-QUANTITATIVE RISK ASSESSMENT MODEL FOR ROTATING EQUIPMENT - WASSAN, RANO KHAN (2014)
The failure of the critical rotating equipment can bring the catastrophic risk for the plant. Therefore, there is a need ofrisk assessment of such critical rotating equipment to reduce risk level. However, previous risk assessment methods, i.e. qualitative, quantitative, semi-quantitative has many restrictions to carry out risk assessment. This study proposed a semi-quantitative risk assessment model to assess the risk ofrotating equipment. It was consisted of three main parts, i.e. risk assessment, Failure Mode and Effect Analysis (FMEA) and maintenance strategy planning. The quantitative risk .matrixwasused for Jhe_ risk assessment of rotating equipment. It was adopted from the MIL-STD882D standard, which was consisted of two basic risk factors, failure rate and failure consequences. Borda ranking method was incorporated to minimize the risk ties that exist in risk matrix ranking. The risk assessment spreadsheet model was developed to automate the risk assessment process.